The Role of BRAF Mutation (V600E) in Papillary Thyroid Carcinoma (PTC) - Azhar Azher M. Al-Ankoshy1, Karrar A. Alqershi2, Hussein W.S. Rabeea3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction. Thyroid cancer is usually associated with genetic alterations. Papillary thyroid carcinoma (PTC) was found to be accompanied by point mutation occurs in a part of exon 15 in specific gene called BRAF which is a part of pathway that responsible for cell main functions such as division. The role of BRAF gene point mutation (V600E) in the occurrence of PTC was investigated in this study.Study designs and subjects: 70 patients previously diagnosed with PTC in addition to 35 controls were recruited in this control-based study. Patients were grouped according to their ages and gender. Blood samples were collected for DNA extraction. PCR was run to detect V600E point mutation in BRAF gene.Results: PTC incidence was found to be higher in patients aged from 40-49 years. The percentage decreased as ages increased. Females had higher PTC frequency than males, 66% to 34%, respectively. The V600E point mutation was detected in 35 patients out of 70 (50%).Conclusion. Genetic studies have to be a part of thyroid cancer investigations. The study confirmed that PTC is usually associated with molecular defect. Other studies such as thyroid profile tests (TSH, T3 or T4) have to be done along with genetic studies for more confirmation and more understanding of this molecular defect.